Desain Pembelajaran Pendidikan Agama Islam Menggunakan Media Digital - Jiwa Wahyu Perdana; Jihaddifa; Gusmaneli (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The use of digital media in Islamic Religious Education (PAI) learning offers various benefits, but also presents challenges. Digital technology creates more interactive and varied learning, giving students greater opportunities for active involvement and independent learning. Digital media enables flexible teaching with broad access to learning materials through e-learning platforms, videos and learning applications. However, limited infrastructure, low digital literacy, as well as security issues and digital distractions are still obstacles. The teacher's role is very important in directing students to choose appropriate content and keeping the learning process safe and effective. For the use of digital media to be successful, a balance between technology and religious values ​​must be maintained. With proper preparation and use, digital media can significantly improve the quality of PAI learning